Mediating Roles of Gratitude and Social Support in the Relation Between Survivor Guilt and Posttraumatic Stress Disorder, Posttraumatic Growth Among Adolescents After the Ya’an Earthquake - Wang, Wenchao; Wu, Xinchun; Tian, Yuxin (Frontiers in Psychology, 2018)
Objective: This study aimed to simultaneously examine the mediating roles of gratitude and social support in the relations between survivor guilt and PTSD, and between survivor guilt and PTG. Method: The present study included 706 adolescents living in Lushan County, China, who were affected by the Ya’an earthquake. The participants completed the self-report questionnaires at three and a half years after the earthquake. Structural equation models were built to examine the roles of survivor guilt, gratitude and social support in PTSD and PTG. Results: The results indicated that survivor guilt had a directly and positive effect on both PTSD and PTG. Gratitude partly mediated the relationship between survivor guilt and both PTSD and PTG; social support partly mediated the relationship between survivor guilt and PTG but not PTSD, as well as the relationship between gratitude and PTG. Conclusions: Survivor guilt has a double-edged sword effect. Survivor guilt had an effect on PTSD and PTG through gratitude, and it could affect PTG but not PTSD through social support. These results suggest that PTSD and PTG are influenced by different mechanisms and that gratitude decrease PTSD and increase PTG, whereas social support increase PTG